2011
DOI: 10.1111/j.1365-2850.2011.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

A hermeneutic approach to the characteristics of mental health nursing practice

Abstract: Mental health nursing (MHN) takes a non-reductionist view of the human being, based on a hermeneutic and interdisciplinary perspective. MHN is dependent on the development of hermeneutic knowledge for understanding the deeper meaning of, for example, encountering a patient with emotional pain. The aim of this study was to provide a philosophical discussion about the characteristics of MHN practice. The hermeneutic approach was used to expand the philosophical discussion of MHN. In order to explore the conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…When the nurses act in accordance with their own values and interests, they can avoid feeling the stress that is often connected with acts of inauthenticity and thus gain positive health benefits. This results is in line with a study among nurses who work in palliative care that showed that authenticity is one of the most important characteristic of professionals [37], and also other studies that emphasized authenticity among nurses to be an important characteristic of professionals in their practice in dealing with patients in various critical conditions [38] [39]. As we mentioned earlier, authenticity in terms of higher-order strengths or capacities has, to our knowledge, not been identified as a personal resource in previous studies dealing with work engagement and staying healthy.…”
Section: Discussionsupporting
confidence: 80%
“…When the nurses act in accordance with their own values and interests, they can avoid feeling the stress that is often connected with acts of inauthenticity and thus gain positive health benefits. This results is in line with a study among nurses who work in palliative care that showed that authenticity is one of the most important characteristic of professionals [37], and also other studies that emphasized authenticity among nurses to be an important characteristic of professionals in their practice in dealing with patients in various critical conditions [38] [39]. As we mentioned earlier, authenticity in terms of higher-order strengths or capacities has, to our knowledge, not been identified as a personal resource in previous studies dealing with work engagement and staying healthy.…”
Section: Discussionsupporting
confidence: 80%
“…Life experience, not just of mental ill health, was something that gave the MHNs credibility and insight. Authenticity or 'use of self' is a common theme in other studies looking at MHNs' perceptions of their role (Hurley 2009, Holm & Severinsson 2011. It is associated with notions of 'the wounded healer', whereby personal insight gives the 'healer' stronger powers to cure fellow sufferers (Zerubavel & Wright 2012).…”
Section: Discussionmentioning
confidence: 99%
“…; Samuelsson et al . ), and that nurses might be in a position to access and affect consumers' intrapersonal experiences (Holm & Severinsson ). Clearly, engaging with consumers in direct, empathic ways to do this might be very challenging and confronting for nurses, requiring them to negotiate both personal and professional ‘demands and boundaries’ (Gilje et al .…”
Section: Discussion and Recommendationsmentioning
confidence: 99%